Argument Strategies and Linguistic Realizations of the Discussion Sections in Local, National, and International Journal Articles in English Education by Indonesian Authors: How do they differ and/or Resemble? - Arsyad, Safnil; Widiarti, Vira; Wulandari, Mega Fitri (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The quality of argument in the discussion section determines the quality of a journal article because in this section authors must argue convincingly so that readers may accept and use their new knowledge claim. This study aims to determine the differences in argument strategies and linguistic realizations in the discussion sections of unaccredited local, accredited national, and reputable international journals in English by Indonesian writers in the field of Language Teaching. The research method used was descriptive qualitative and quantitative research methods (mixed-method) in analyzing differences in argument styles and linguistic features of the discussion sections of the journal articles. Sixty articles were analyzed using the genre-based text analysis method following Swales (1990) and Dudley Evan (1994). The results show that the argument strategies of articles in local, national, and international journals have important differences. The main differences are the discussion sections in the international journals are much longer in word count and use much more references than the local and national journals do. Also, unlike international journal articles, the majority of local journals use an incomplete argument strategy while national journal articles use a semicomplete argument strategy. Yet another difference is that international journal authors tend to use non-integral citations more frequently while local and national journal authors prefer using integral citation types. The similarity among the three journal articles is that the majority of the authors tend to use present tense and past tense in their discussion section rather than present perfect tense and future tense.Â Keywords: argument strategy, Research article, comparative rhetorical Â study